2017
DOI: 10.4103/ijpvm.ijpvm_246_16
|View full text |Cite
|
Sign up to set email alerts
|

Alloimmunization in thalassemia patients: New insight for healthcare

Abstract: Background:Development of alloantibodies against the foreign red blood cell (RBC) (alloimmunization) is a well-known complication in thalassemia patients when performing multiple transfusions. The study was conducted to know the prevalence of alloimmunization in thalassemia patients, in the Caspian Sea coastline.Methods:This study is a descriptive, retrospective analysis of transfusion records of 190 patients with β-thalassemia major who received regular transfusions. To detect the type of alloantibodies, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 17 publications
1
34
0
9
Order By: Relevance
“…Aromaterapi merupakan pengobatan yang holistik, memanfaatkan minyak esensial yang diekstrak dari tanaman aromatik seperti dari bunga, rempah-rempah, buah-buahan, kayu, dan daun untuk menciptakan keseimbangan dan harmoni pada tubuh, pikiran, dan jiwa. 11 Penelitian lain yang dilakukan di Puskemas wilayah Semarang menggunakan minuman jahe dan aromaterapi esensial lemon sama efektifnya dalam menurunkan intensitas mual muntah pada ibu hamil. 12 Penelitian yang dilakukan di Puskesmas Alak ada perbedaan yang signifikan pada frekuensi mual muntah terhadap ibu hamil sebelum dan setelah pemberian minuman sari jahe bagi ibu hamil.…”
Section: Metodeunclassified
“…Aromaterapi merupakan pengobatan yang holistik, memanfaatkan minyak esensial yang diekstrak dari tanaman aromatik seperti dari bunga, rempah-rempah, buah-buahan, kayu, dan daun untuk menciptakan keseimbangan dan harmoni pada tubuh, pikiran, dan jiwa. 11 Penelitian lain yang dilakukan di Puskemas wilayah Semarang menggunakan minuman jahe dan aromaterapi esensial lemon sama efektifnya dalam menurunkan intensitas mual muntah pada ibu hamil. 12 Penelitian yang dilakukan di Puskesmas Alak ada perbedaan yang signifikan pada frekuensi mual muntah terhadap ibu hamil sebelum dan setelah pemberian minuman sari jahe bagi ibu hamil.…”
Section: Metodeunclassified
“…While, it seems that only a moderate score of DQI-I is enough to reduce 8-iso- (49,50). We further indicated that greater adherence to the HEI-2015 had favorable effects on serum HDL level and LDL/HDL ratio, respectively, which can be due to high intake of cardio protective micro-nutrients irrespective of differences in genotypes of ApoB SNPs (45). In addition, serum HDL concentration was signi cantly higher in E-allele carriers in ApoB EcoR1 SNP than E + E + homozygous.…”
Section: Discussionmentioning
confidence: 68%
“…Currently, there is no experimental or human study on the interaction between genetic pro le and DPI on cardio metabolic parameters. However, some researched have demonstrated the reducing effect of DPI on in ammation, obesity and pre-diabetes (19,45). Furthermore, the interaction between dietary patterns or components and ApoB SNPs on oxidative stress and anti-oxidative markers has not been investigated, yet.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no experimental or human study on the interaction between genetic pro le and DPI on cardio metabolic parameters. However, some researched have demonstrated the reducing effect of DPI on in ammation, obesity and pre-diabetes 15,42 . Furthermore, the interaction between dietary patterns or components and ApoB SNPs on oxidative stress and anti-oxidative markers has not been investigated, yet.…”
Section: Discussionmentioning
confidence: 99%